Hiroshima no pika - Maruki, Toshi, 1912- (New York : Lothrop, Lee & Shepard, 1980)
A retelling of a mother's account of what happened to her family during the "Flash" that destroyed Hiroshima in 1945.
Translation of: Hiroshima no pika (i.e. The flash of Hiroshima).
Elem. School Library Collection.
Wilson's Children.
Wilson's Junior High School.
4.8
5-8
Keywords: Atomic bomb -- Japan -- Hiroshima-shi -- Juvenile literature; World War, 1939-1945 -- Japan -- Juvenile literature; Atomic bomb; World War, 1939-1945 -- Japan; Atomic bomb; World War, 1939-1945 -- Japan; Hiroshima-shi (Japan) -- History -- Bombardment, 1945 -- Juvenile literature; Japan -- History -- 1912-1945 -- Juvenile literature; Hiroshima-shi (Japan) -- History -- Bombardment, 1945.; Japan -- History -- 1912-1945.; Hiroshima-shi (Japan) -- History; Japan -- History -- 1868-1945.